MULTILAYER POROUS COMPOSITE FROM WASTE GLASS FOR WATER FILTRATION - Aji, M. P.; Wiguna, P. A.; Rosita, N.; Susanto, S.; Savitri, M. I.; Said, M. A.N.; Sulhadi, S. (Physics Department, Faculty of Mathematics and Natural Sciences, Semarang State University, 2015)
Multilayer porous composite have been produced through the heating process at temperature T=700oC for 2.5 h. Single layered porous composite was made with a varied mass percentage of from PEG polymer 1% to 10%. Double-layered porous composite were made by the arrangement of porosity (4:3)%, (4:2)% and (3:2)%, while the three-layers porous composite have an arrangement (4:3:2)%. Performance of multilayer porous composite for water filtration with pollutants of methylene blue 100 ppm was estimated from the absorbance spectrum. Rejection of methylene blue pollutants from single layered porous composite increases when the fraction of PEG polymer tend to be smaller in the matrix. Meanwhile, the double layered porous composite has a degradation of methylene blue pollutants are better than one layer. Triple layered porous composite have good performance for the water filtration where all the pollutants of methylene blue be able to be filtered. Komposit pori berlapis telah dihasilkan dengan proses pemanasan pada temperatur T=700oC selama 2.5 jam. Komposit pori satu lapis dibuat dengan variasi persen massa polimer PEG 1% hingga 10%. Komposit pori dua lapis dibuat dengan susunan porositas (4:3)%, (4:2)% dan (3:2)%, sedangkan komposit pori tiga lapis memiliki susunan porositas (4:3:2)%. Kinerja komposit pori berlapis untuk filter air dengan polutan methylene blue 100 ppm diestimasi dari spektrum absorbansi. Rejeksi polutan methylene blue dari komposit pori satu lapis meningkat saat fraksi polimer PEG cenderung lebih kecil dalam matrik komposit. Sedangkan, komposit pori dua lapis memiliki kemampuan untuk degradasi polutan methylene blue yang lebih baik dari satu lapis. Komposit pori tiga lapis memiliki kinerja yang baik untuk filter air dimana seluruh polutan methylene blue mampu disaring.